Care Culture as a Meaning-Making Process: A Study of a Mistreatment Investigation. (September 2013) - Rytterström, Patrik; Unosson, Mitra; Arman, Maria
Culture might offer significant insights into the circumstances under which mistreatment occurs. Our aim with this study was to understand and explore institutional mistreatment from a care culture perspective. We used a case study with a triangulating methodology. It involved 12 individual interviews, one focus group interview with four people, a 2-day field study, and a document study. The case was a mistreatment situation that had occurred in municipal care, in which residents had been locked in their rooms at night. Two different care cultures were identified that could give a richer contextual understanding of the motives behind the institutional mistreatment. The service culture was need-oriented and emphasized freedom in care provision. The motherhood culture was characterized by protection and safeguarding of the vulnerable residents. Both cultures showed traces of caring values, but when important caring values were absent, this created a seedbed for mistreatment.